(untitled) (Kinesiology, 2017)
Volume, or the total work performed during resistance training is one of the vital variables of resistance exercise programming. The most common definition in use by practitioners is sets x reps x external weight. While appropriate for linear loading incurred through free-weight resistance exercise, this inadequately addresses the nonlinear loading incurred with rubber resistance, a relatively new loading technique. The purpose of this investigation was to derive a theoretical model to describe a method of volume calculation for rubber band plus free-weight exercise. Men (n=51; age 19.5±1.6 years; body height 1.76±0.07 meters; body weight 77.3±11.3 kilograms) and women participants (n=66; age 18.9±1.1 years; body height 1.65±0.07 meters; body weight 62.8±9.1 kilograms) were measured for band lengths incurred at: squat with knee extended position, squat with flexed position, and change in band length was then calculated. Significant gender differences were seen for band length change as a percentage of body height (p<0.5) during the squat, which mandated separate volume equations (females=33.8%; males=35.3% of body height). Equations were determined for total external volume estimation in kgm=[0.338(m+2c2+(ln(h)-0.383)2c1)]/g and kgm=[0.352(m+2c2+(ln(h)-0.382)2c1)]/g for females and males, respectively, where m is the total external resistance, c2 and c1 are constants derived from rubber-band loading parameters, h is the body height of the participant, and g is gravitational acceleration. This work provides practitioners and researchers with a simple theoretical method for work estimation using participant’s body height to estimate displacement values during the squat exercise. Key words: variable resistance, material properties, reliability, intra-repetition